Cytotoxic potential on human breast and lung cancer cells of the biosynthesized gold nanoparticles from the reduction of chloroauric acid by lactic acid isolated from Lactobacillus acidophilus - Repotente, Elmer Casley; Carreon, Angelo Jose; Devanadera, Mark Kevin; Esmalla, Maria Salvacion; Santiago-Bautista, Myla (Frontiers in Materials, 2022)
Chemotherapy side effects, drug resistance, and tumor metastasis hinder the progress of cancer treatments which has led to cancer patients having a poor prognosis. In recent years, nanoparticles (NPs) have been an emerging trend in drug delivery technology. The biosynthesis of gold nanoparticles (AuNPs) from lactic acid as probiotic metabolites is a cost-efficient and eco-friendly approach due to the widespread availability and ease of culturing methods. Here, AuNPs were synthesized by reducing chloroauric acid using lactic acid isolated from the probiotic, Lactobacillus acidophilus. Surface characterization of the biosynthesized was performed using UV-Visible spectroscopy, Field Emission Scanning Electron Microscopy with Energy Dispersive Spectroscopy (FESEM-EDS), and Atomic Force Microscopy (AFM). The distinct peak of the AuNPs in the UV-Vis spectra at around 520 nm indicates the nanoscale level of the gold particles. SEM images of the shape of the biosynthesized AuNPs was found to be small, smooth spherical particles with sizes ranging from 6-12 nm. AFM results agree with SEM images, showing AuNPs with sizes ranging from 4 to 15 nm. The anticancer activities of the biosynthesized AuNPs have been investigated using cytotoxicity (MTT) and apoptosis (Caspase 3/7) assay in the human breast, lung cancer cells (MCF7 and A549), and control (Myoblasts). MTT assay showed AuNPs’ cytotoxic potential on cancer cells (MCF7 and A549) compared to normal cells (Myoblasts). Cytotoxicity and apoptosis assay of the synthesized AuNPs exhibits toxicity against human breast adenocarcinoma cells (MCF7, IC50 of 0.075 mM) and human lung cancer cells (A549, IC50 of 0.07mM) as shown evidently in the cellular morphology and in DNA-stained nucleus. Only MCF7 cells exhibited apoptotic events upon AuNPs treatment. AuNPs proved to be safe as it is non-toxic against normal cells and myoblasts. Interestingly, the biosynthesized AuNPs were absorbed by the cells and present in the cytosol, thus, demonstrating selectivity towards breast and lung cancer cells used. The study showed the first evidence that AuNPs can be synthesized using lactic acid as a reducing agent and capping agent isolated from the probiotic, Lactobacillus acidophilus. The results suggested potential cancer chemotherapeutic leads and targeted delivery in human breast and lung cancer.